1972
DOI: 10.1149/1.2404142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Processes of Formation of Lead-Acid Battery Positive Plates

Abstract: The processes involved in the formation of the positive lead-acid battery plate in H2SO4 with sp gr 1.15 and 1.05 and in 0.7M Na2SO4 were studied by x-ray diffraction, wet chemical analysis, and microscopic observations. It was found that formation takes place in two stages. During the first one, H2SO4 and H20 penetrate from the bulk of the solution into the plate. As a result of chemical and electrochemical reactions tet-PbO and basic sulfates of lead are converted to PbSO4 and a-PbO2. These compounds form zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…It is well known that the AM of the freshly formed positive and negative plates mainly consists of ␣/␀-PbO 2 and Pb, respectively [22,23]. After the end of cycle life test, Fig.…”
Section: Teardown Analysismentioning
confidence: 99%
“…It is well known that the AM of the freshly formed positive and negative plates mainly consists of ␣/␀-PbO 2 and Pb, respectively [22,23]. After the end of cycle life test, Fig.…”
Section: Teardown Analysismentioning
confidence: 99%
“…Reference [9] has shown that in acidic solutions, when lead-acid battery is charged, the materials next to the grid are first converted to conductive lead and lead dioxide. Formation then proceeds inward toward the center of the pellet.…”
Section: E Figures Battery Level Studiesmentioning
confidence: 99%
“…Pavlov and collaborators in their papers [4,7,8] have shown that the formation of the positive plates in which changes were made in the phase and in the chemical composition of the mature paste in them, occurs in two stages.…”
Section: Introductionmentioning
confidence: 99%
“…In papers [4,6,7,9] it has been shown that in the reactions during When applying ultrasonic waves during the formation of the positive plates of the lead batteries some conditions are created for the exchange of the electrolyte in the pores of the plates and the electrolyte in the cell volume. The improved conditions for the exchange of the electrolyte in the pores of the positive plates and electrolyte volume in the cell that have different concentrations, leads to a higher contents of bPbO 2 in these areas compared to the contents of bPbO 2 in the positive plates, which have been formed without the application of ultrasonic waves.…”
Section: Introductionmentioning
confidence: 99%